A Historical Review of Medical Robotic Platforms. (30th January 2021) - Ginoya, Tirth; Maddahi, Yaser; Zareinia, Kourosh
Abstract : This paper provides a brief history of medical robotic systems. Since the first use of robots in medical procedures, there have been countless companies competing to developed robotic systems in hopes to dominate a field. Many companies have succeeded, and many have failed. This review paper shows the timeline history of some of the old and most successful medical robots and new robotic systems. As the patents of the most successful system, i.e., Da Vinci® Surgical System, have expired or are expiring soon, this paper can provide some insights for new designers and manufacturers to explore new opportunities in this field.